Performance data analysis Olympic Games - Tokyo 2020: Overview of the most important technical parameters of the Tokyo Olympic Games - Dokmanac, M. (International Journal of Wrestling Science, 2021)
The next few pages will present the most important technical data from the Tokyo 2020 Olympic Games. All this data is available through the "performance data analysis" platform at the internet address http://uww.io/wpar. This analysis provides basic information about the current state of world wrestling. The disadvantage is that this type of analysis has not been done continuously in the past. A comparison with the European championship 2020 was made for the three most important data. It would be best to make a comparison of the last 3 world championships and the last Olympic games.